MS training kit- MS Windows 2000 network infrastructure administration - Microsoft Corporation (New Delhi Prentice-Hall of India, 2001)
Official Microsoft study guide for the skills on the job and exam. Learn how to deliver, secure and reliable networking services for organization and to prepare for the Microsoft Certified Professional(CMCP)exam. Work at your own pace-through the lessons
Keywords: Microsoft software-Examinations-Study guides; Electronic data processing personnel-Certification; Directory services (Computer network technology)-Examinations-Study guides